The chemical, microbiological and sensory evaluation of three samples of drinking water in three localities in Khartoum North Sudan - Onsa, Zeinab Osman; Ahmed, Waheeba El-Faki; Razig, Kamal Awad Abdel (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2017)
The samples of water were taken from Elhag yousef, Caffori and Dardog localities (ground water).The chemical analysis proved that Elhag yousef and Dardog water samples possess hard ness of 199mg/While Cafori was 100mg/l The samples of water were subjected to bacteriological analysis, using most probable number (MPN) test. These examinations showed no detection of total coliform, fecal coliform and fecal streptococci. The result showed no detection of the mineral carbonate in all the three samples. Sensory evaluation cleared that Elhag yousif water sample is the worst in taste, texture, flavor appearance and general acceptability compared with the other samples